Interactive association of lipopolysaccharide and free fatty acid with the prevalence of type 2 diabetes: A community‐based cross‐sectional study. Issue 6 (3rd May 2019) - Huang, Xiuji; Yan, Dan; Xu, Mingtong; Li, Feng; Ren, Meng; Zhang, Jin; Wu, Muchao
Abstract: Aims/Introduction: Increased blood lipopolysaccharide (LPS) or free fatty acid (FFA) levels correlate with an increased risk of type 2 diabetes. The purpose of the present study was to evaluate the interactive effect of serum LPS and FFA levels on the prevalence of type 2 diabetes. Materials and Methods: This cross‐sectional study included 2, 553 community‐dwelling Chinese adults. Fasting serum LPS levels were determined using the Limulus Amebocyte Lysate Chromogenic Endpoint assay, and FFA levels were determined using an enzymatic method. The participants were divided into three groups according to the tertiles of LPS or FFA levels or nine groups according to the tertiles of LPS and FFA levels. The odd ratios (ORs) for type 2 diabetes were estimated using logistic regression analysis. Results: We found that higher serum LPS or FFA levels were associated with higher high‐sensitivity C‐reactive protein levels ( P < 0.001), homeostatic model assessment of insulin resistance levels ( P < 0.001) and ORs for type 2 diabetes ( P < 0.01). Meanwhile, there were significant interactions between LPS and FFA in terms of the high‐sensitivity C‐reactive protein level ( P < 0.001), homeostatic model assessment of insulin resistance level ( P < 0.001) and ORs for type 2 diabetes ( P < 0.001). In the fully adjusted logistic regression model, the OR for participants with type 2 diabetes in the higher LPS and FFA level group were 6.58 (95% confidence interval 3.05–14.18, P < 0.001) compared with that in participants in the lower LPS and FFA level group. Conclusions: The interaction between LPS and FFA was associated with an increased risk of type 2 diabetes in community‐dwelling Chinese adults. Abstract : We, for the first time, showed that the interaction between lipopolysaccharide and free fatty acids is associated with higher systemic inflammation levels, insulin resistance levels and a higher prevalence of type 2 diabetes in the Chinese population. Further studies to validate our findings and clarify the mechanisms would provide a more effective alternative for improving inflammation and IR, and thereby the treatment and/or prevention of type 2 diabetes.